2015
DOI: 10.1007/s11764-015-0467-6
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of self-management for post treatment cancer survivors: evaluation of a risk-adapted visit

Abstract: Combined provision and discussion of SCPs help survivors construct a useful understanding of their cancer experience and may promote long-term self-management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Self-management can empower cancer survivors to report and manage potential late and long-term effects of treatment, understand when to seek support, and make lifestyle changes to promote healthy living after treatment (Foster and Fenlon, 2011). The CCM model addresses survivors’ goals/preferences and fosters confidence in their ability to perform care activities (Rosenberg et al, 2015). It coaches survivors on key self-management skills such as problem-solving, decision-making, taking action or goal-setting, communication with providers, regular assessment of progress, and resource utilization (Klabunde et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Self-management can empower cancer survivors to report and manage potential late and long-term effects of treatment, understand when to seek support, and make lifestyle changes to promote healthy living after treatment (Foster and Fenlon, 2011). The CCM model addresses survivors’ goals/preferences and fosters confidence in their ability to perform care activities (Rosenberg et al, 2015). It coaches survivors on key self-management skills such as problem-solving, decision-making, taking action or goal-setting, communication with providers, regular assessment of progress, and resource utilization (Klabunde et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Current studies have shown that self‐management support is significant in stoma care (Hong & Wang, ), because it can enhance self‐efficacy (Zhang et al, ) and guide future self‐management behaviour (Rosenberg et al, ). Most studies focused on the content of health education or self‐care ability for a certain symptom (e.g., defecation management of patients with a stoma or the effects on self‐management education).…”
Section: Introductionmentioning
confidence: 99%
“…Current studies with colorectal cancer patients have shown that self-management support can enhance self-efficacy22 and can help with ostomies adapt to their stoma23 and to guide future self-care behavior 24. On the other hand, lower self-efficacy was significantly associated with poorer trajectories for QoL, health status, and well-being after adjusting for disease characteristics, stoma, anxiety, and social support 25…”
Section: Introductionmentioning
confidence: 99%